Unraveling Treatment of Currency Translation, Foreign Exchange Gains and Losses under Ethiopian Income Tax Law - Alemayehu, Eyader Teshome (Bahir Dar University Journal of Law, 2024)
The issue of currency conversion in taxation and tax treatment of foreign exchange gain or loss is one of the nascent, yet complex and controversial area requiring due consideration from policy makers and legislative bodies. The legal requirement of assessment and final payment of tax liability in domestic currency has brought to the forefront the rule of currency translation when transaction is made in foreign currencies. This in turn has the potential for impending gains or losses in foreign exchange that emanate either from fluctuation in the rate of exchange among currencies or government measures of devaluation and revaluation of currency. A tax treatment of such gain and loss necessitates an effective legal framework to neutralize the negative effects of exchange fluctuation. As a result, tax laws of different countries govern and regulate comprehensively tax implications of transactions denominated in foreign currency. A concern might arise as to whether the Ethiopian income tax law ensures neutrality, clarity and certainty in relation to those issues. This research explores tax implication of foreign exchange gains and losses under Ethiopian income tax laws. The research is a doctrinal legal research type carried out through a comparative method. The evidence from the investigation shows that a number of uncertainties and anomalies surround the existing Ethiopian income tax law regarding method as well as time of exchange rate in currency translation rule, the time of recognition of foreign exchange gains and losses, and as to how and when to determine realization. Moreover, there is an apparent discrepancy and even contradiction between Income Tax Proclamation No.979/2016 and Regulation No.410/2017 (amended by Regulation No.485/2021). Discrepancies can also be read between the Amharic and English versions of the laws. Taking cognizance of those glitches, either the law must be revised or the tax authorities at federal and regional levels have to come up with explanations through directives or advance rulings.